PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS DIGITAL MENGGUNAKAN APLIKASI CAPCUT PADA PEMBELAJARAN IPAS MATERI PERUBAHAN BENTUK ENERGI DI KELAS III SEKOLAH DASAR - Neni Wulandari Oktavia Ningrum; Zuryanty; Putri Zulkarnaini, Aissy; Chandra (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The background of this study is the limited variety of learning media used by teachers in the IPAS learning process in Grade III of elementary school, which causes students to experience difficulties in understanding the conceptual topic of Energy Transformation. This study aims to develop digital-based learning media using the CapCut application that meets the criteria of validity, practicality, and effectiveness. This research is classified as Research and Development (R&D) using the ADDIE model, which consists of the stages of Analysis, Design, Development, Implementation, and Evaluation. The research subjects were Grade III students and teachers at SDN 13 Kapalo Koto, SDN 09 Koto Luar, and SDN 07 Binuang Kampung Dalam. The research instruments included validation sheets from material, language, and media experts, teacher and student response questionnaires, and learning outcome tests in the form of pretest and posttest. The results of the analysis show that the developed digital learning media using the CapCut application achieved a validity score of 95.83%, which is categorized as highly valid. The practicality results based on teacher responses obtained percentages of 95%, 97.5%, and 100%, while student responses obtained 87.96%, 88.98%, and 88.13%, all of which are categorized as highly practical. The effectiveness results based on the N-Gain scores were 0.73, 0.79, and 0.75, categorized as highly effective. Therefore, the digital learning media developed using the CapCut application is proven to be valid, practical, and effective in teaching Energy Transformation material in Grade III of elementary school.